Abu Ali Al-Farsi’s Grammatical Objections to Al-Zajjaj in the Parsing of Surah An-Nisa: A Study in the Book of Omissions - Jassim Al-Jubouri, Salam Abdul (Journal of Tikrit University for Humanities, 2024)
Sheikh Abu Ishaq Al-Zajjaj’s grammatical directions for the words of the Holy Qur’an in his famous book, The Meanings of the Qur’an and Its Parsing are extensive and characterized by accuracy and intelligence. However, many of these directions were not well received by his student Abu Ali Al-Farsi, and from his point of view, they are in need of reform. In this regard, he wrote his book entitled Reconciled Issues from the Book of the Meanings of the Qur’an and its Parsing by Abu Ishaq Al-Zajjaj, which was later known among scholars as: (The Omission). There are two questions that impose themselves in this context, the first of which is: (Is everything that the Persian sees? That it needed reform (did it really need that reform)? As for the second question, it can be formulated as follows: (Was everything he corrected from Al-Zajjaj’s words successful in it)? In order to answer these two important questions and to determine the truth of Al-Farsi’s objections to his sheikh Al-Zajjaj.